Multiple damage detection in laminated composite beams using automated model update. (December 2021) - Kahya, Volkan; Okur, Fatih Yesevi; Karaca, Sebahat; Altunışık, Ahmet Can; Aslan, Mustafa
Abstract: This paper presents damage identification and localization in laminated composite beams including multiple cracks by automated model updating. For this aim, a cantilever beam made of glass/epoxy composite laminate under six simulated damage scenarios is considered. Experimental frequencies and mode shapes of the beam are validated with those of ANSYS® finite element analyses. For damage detection and localization, FEMtools®, a software for automated model updating, is employed. To simulate damages in FEMtools®, material moduli and mass density of the beam are chosen to be uncertain parameters, and the sensitivity analysis based on the Bayesian parameter estimation is performed. In-plane material moduli are found to be the most sensitive parameters for damage evaluation in composite laminates. The locations of the cracks are determined by evaluating the changes (decrease) in these parameters. According to the results of the study, the proposed method can locate the multiple cracks of different severity for the considered cantilever beam. However, in the case with multiple damages of equal severity, only the crack nearest to the fixed-end can be successfully determined while others cannot because the existence of damage near the support in cantilever beams obscures the effects of other damages and the method fails to identify them.